Changes in Ocular Manifestations of Behçet Disease in Korean Patients over Time: A Single-center Experience in the 1990s and 2000s. (April 2015) - Chung, Yoo-Ri; Lee, Eun-So; Kim, Min Ho; Lew, Ho Min; Song, Ji Hun
Abstract Purpose: To analyze chronological changes in ocular manifestations of Behçet's disease (BD) in Korean patients. Methods: Ocular findings were retrospectively analyzed from medical records of patients diagnosed with BD between 1994 and 2010 and divided into two groups according to the date of their first visit to our ophthalmology department. Group A began care between 1994 and 2000, and Group B between 2004 and 2010. Results: Fifty-six patients (83 eyes) were included in analyses. There was a significant decrease in the number of complete BD cases in Group B compared to Group A, and fewer patients had genital lesions in Group B. Mean visual acuity was better, and more patients had good vision in Group B than in Group A at the one and two year follow-up. Conclusions: The severity of BD has decreased over the past two decades, allowing BD patients with ocular involvement to have better visual prognoses.